Challenges for Educators in the Independent Curriculum at SMAN 1 Sakra - Destia Ira Pratiwi; Aulia Laela Rahmah; Eyis Hariati Paramita Ningsih (al-Afkar, Journal For Islamic Studies, 2026)
This study discusses the challenges faced by educators in implementing the Merdeka Curriculum at SMAN 1 Sakra. The Merdeka Curriculum aims to enhance education through P5-based learning (projects to strengthen the profile of Pancasila students), which focuses on developing students' character and competencies. The Merdeka Curriculum provides students with the freedom to develop their creativity. Despite this freedom, educators still supervise to ensure that the learning objectives are achieved. The results of the study indicate that educators face challenges in implementing the Merdeka Curriculum, such as in the learning process, understanding the core concepts and principles of the curriculum, guiding students, addressing student difficulties in project-based learning, observing changes in students after implementing the curriculum, and devising strategies to foster independent learning and achieve learning outcomes. It is hoped that the school can provide attention and support to develop and improve the implementation of the Merdeka Curriculum at SMAN 1 Sakra.